2015
DOI: 10.1111/aas.12665
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of spinal anaesthesia with bupivacaine or 2‐chloroprocaine during caesarean section

Abstract: 2-Chloroprocaine can be used for low risk Caesarean section in healthy parturients. There is no difference in time to motor block resolution compared to bupivacaine. Motor recovery seems more predictable for 2-chloroprocaine and may be beneficial for the breastfeeding initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…1 In addition, to our knowledge, since no study on intrathecal HP has reported before the time to T4 dermatome, we believed that 15 min delay was consistent with the results concluded on bupivacaine for CS, varying between 4 and 12 min. 4,37,38 Overall, surgical anesthesia was effective in 35 of 40 patients (87.50%), for the prede ned assessed doses, which can be consider as a high success rate comparing with reported results on other local anesthetics. 10,39 Interestingly, our results provide evidence that a dose of HP between 45 and 50 mg is su cient to ensure surgical anesthesia to a T4 sensory level, which is in fact lower comparing to the doses reported by previous dose-nding studies.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…1 In addition, to our knowledge, since no study on intrathecal HP has reported before the time to T4 dermatome, we believed that 15 min delay was consistent with the results concluded on bupivacaine for CS, varying between 4 and 12 min. 4,37,38 Overall, surgical anesthesia was effective in 35 of 40 patients (87.50%), for the prede ned assessed doses, which can be consider as a high success rate comparing with reported results on other local anesthetics. 10,39 Interestingly, our results provide evidence that a dose of HP between 45 and 50 mg is su cient to ensure surgical anesthesia to a T4 sensory level, which is in fact lower comparing to the doses reported by previous dose-nding studies.…”
Section: Discussionmentioning
confidence: 56%
“…The de nition of a successful block differs widely amongst dose-nding studies having investigated the potency of intrathecal local anesthetics for cesarean section. 1,10,[35][36][37] In this study, we de ned as "success" the combination of a bilateral T4 attained sensory level obtained within 15 min after intrathecal HP dose administration with no pain experienced upon incision and until the end of surgery. We did this choice for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of a successful block differs widely amongst dose-finding studies having investigated the potency of intrathecal local anesthetics for cesarean section [1,10,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…3 Neuraxial anaesthesia and general anaesthesia can be performed in caesarean section. 4 , 5 However, in clinical practice, some anaesthetics (e.g., opioids) have a potential for respiratory depression of neonates, 6 which leads to a decrease in Apgar scores and pH values. If the neonatal Apgar score is < 7 at 5 min or pH is < 7.20, newborns are admitted to the neonatal intensive care unit.…”
Section: Introductionmentioning
confidence: 99%